1996
DOI: 10.1152/ajpregu.1996.271.3.r545
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage and antioxidants in Rana sylvatica, the freeze-tolerant wood frog

Abstract: Freeze-tolerant wood frogs (Rana sylvatica) must endure prolonged ischemia on freezing. Reperfusion on thawing brings with it the potential or oxidative damage due to reactive oxygen species formation, a well-known consequence of mammalian ischemia-reperfusion. To determine whether oxidative damage occurs during thawing and how frogs deal with this, we examined oxidative damage and antioxidant and prooxidant systems in tissues of Rana sylvatica and a nonfreezing relative, Rana pipiens. Glutathione status indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
3
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(125 citation statements)
references
References 0 publications
8
109
3
5
Order By: Relevance
“…Changes in the activities of antioxidant enzymes have been found in many organisms in response to anoxia (Hermes-Lima and Storey, 1993;Hermes-Lima and Storey, 1996;Pannunzio and Storey, 1998;Lushchak et al, 2001), freezing (Hermes-Lima and Storey, 1993;Joanisse and Storey, 1996) and also Antioxidant defence and stress protein induction following heat stress in the Mediterranean snail Xeropicta derbentina Sandra Troschinski*, Andreas Dieterich, Stefanie Krais, Rita Triebskorn and Heinz-R. Köhler heat stress (Heise et al, 2006;Lushchak and Bagnyukova, 2006a;Verlecar et al, 2007). An increase in antioxidants during aestivation in snails (Hermes-Lima et al, 1998;Ramos-Vasconcelos and HermesLima, 2003;Nowakowska et al, 2009) has also been shown.…”
Section: Research Articlementioning
confidence: 99%
“…Changes in the activities of antioxidant enzymes have been found in many organisms in response to anoxia (Hermes-Lima and Storey, 1993;Hermes-Lima and Storey, 1996;Pannunzio and Storey, 1998;Lushchak et al, 2001), freezing (Hermes-Lima and Storey, 1993;Joanisse and Storey, 1996) and also Antioxidant defence and stress protein induction following heat stress in the Mediterranean snail Xeropicta derbentina Sandra Troschinski*, Andreas Dieterich, Stefanie Krais, Rita Triebskorn and Heinz-R. Köhler heat stress (Heise et al, 2006;Lushchak and Bagnyukova, 2006a;Verlecar et al, 2007). An increase in antioxidants during aestivation in snails (Hermes-Lima et al, 1998;Ramos-Vasconcelos and HermesLima, 2003;Nowakowska et al, 2009) has also been shown.…”
Section: Research Articlementioning
confidence: 99%
“…Freeze exposure for 24 h in the wood frog Rana sylvatica prompted significant increases in Se-GPX and total-GPX activities in different tissues (Joanisse and Storey 1996). Increased expression of thioredoxin, glutathione S-transferase (GST), and glucose-6-phosphate dehydrogenase (G6PDH) in heart and g-glutamyltranspeptidase (g-GT) activity in liver were also observed for wood frogs under exposure to freezing (Hemmings and Storey 1996;Storey 2004).…”
Section: Oxidative Stress In Hypoxic/anoxic-tolerant Speciesmentioning
confidence: 99%
“…Moreover, Se-GPX activity increased on sub-zero freezing (a hypometabolic condition that imposes ischemia on internal organs; Storey, 1996) in garter snakes (Hermes-Lima and Storey, 1993a) and wood frogs (Joanisse and Storey, 1996) and under severe dehydration in leopard frogs (50% loss of body water after 92 h, at 5°C, causing ischemia in internal organs; Hermes-Lima and . Moreover, Se-GPX activity from the hepatopancreas of the freshwater snail B. tenagophila (control activity, 10 mi.u.…”
Section: Antioxidant Enzymes and Gsh In Estivating H Aspersamentioning
confidence: 99%